2014
DOI: 10.1107/s2053229614010195
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen ADPs with CuKα data? Invariom and Hirshfeld atom modelling of fluconazole

Abstract: For the structure of fluconazole [systematic name: 2-(2,4-difluorophenyl)-1,3-bis(1H-1,2,4-triazol-1-yl)propan-2-ol] monohydrate, C13H12F2N6O·H2O, a case study on different model refinements is reported, based on single-crystal X-ray diffraction data measured at 100 K with Cu Kα radiation to a resolution of sin θ/λ of 0.6 Å(-1). The structure, anisotropic displacement parameters (ADPs) and figures of merit from the independent atom model are compared to `invariom' and `Hirshfeld atom' refinements. Changing fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…It is based on the least-squares refinements of coordinates and atomic displacement parameters using aspherical atomic scattering factors which are obtained from Hirshfeld's stockholder partitioning (Hirshfeld, 1977) of the molecular electron density. It is found that the HAR-refined structures are significantly improved compared with the independent atom model (IAM), especially in the case of positions and displacement parameters of hydrogen atoms (Woiń ska et al, 2014(Woiń ska et al, , 2016Orben & Dittrich, 2014). Herein, HAR has been applied to test its performance for the Hg-H bond distance determination from theoretical structure factors in the case where two hydrogen atoms are directly bonded to a 5d transition metal (mercury in this case).…”
Section: Appendix C Hirshfeld Atom Refinementmentioning
confidence: 99%
“…It is based on the least-squares refinements of coordinates and atomic displacement parameters using aspherical atomic scattering factors which are obtained from Hirshfeld's stockholder partitioning (Hirshfeld, 1977) of the molecular electron density. It is found that the HAR-refined structures are significantly improved compared with the independent atom model (IAM), especially in the case of positions and displacement parameters of hydrogen atoms (Woiń ska et al, 2014(Woiń ska et al, , 2016Orben & Dittrich, 2014). Herein, HAR has been applied to test its performance for the Hg-H bond distance determination from theoretical structure factors in the case where two hydrogen atoms are directly bonded to a 5d transition metal (mercury in this case).…”
Section: Appendix C Hirshfeld Atom Refinementmentioning
confidence: 99%
“…29 Therefore, the experimentally refined structure obtained with HAR is normally much improved compared to IAM, especially pertaining to the positions and displacement parameters of hydrogen atoms. [109][110][111] Currently, HAR is possible with aspherical scattering factors from HF and BLYP calculations. In this study, we have not accounted for PCE correction inside the quasirelativistic IOTC HAR approach.…”
Section: Pce and Relativity Remarksmentioning
confidence: 99%
“…In this work, we discuss the influence of the applied model of electron density ( Section 3.2 ), the approach to modelling hydrogen atom ADPs ( Section 3.3 ), and the source of radiation ( Section 3.4 ) on the parameters of charge density distribution. Some of these aspects were discussed in previous studies; for instance, the influence of H-atom ADPs on charge density results [ 13 , 14 ], the application of low-resolution Cu Kα data [ 12 , 15 , 16 ], and the differences between quantum crystallography models [ 17 , 18 , 19 , 20 , 21 , 22 ]. In this complementary work, we consider the effects of the refinement of hydrogen atoms with the NoMoRe method, as well as the influence of the source of radiation (with the same resolution).…”
Section: Introductionmentioning
confidence: 99%